2017
DOI: 10.1097/dcr.0000000000000800
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of a Grading System for Anastomotic Leakage After Low Anterior Resection: Analysis From a National Cohort Database

Abstract: Anastomotic leakage after low anterior resection for rectal cancer was a frequent observed complication in this cohort. Differences in clinical outcome suggest that grade B and C leakage should be considered separate entities in future registrations. In patients with a diverting stoma, the chances of experiencing grade C anastomotic leakage were reduced. See Video Abstract at http://links.lww.com/DCR/A315.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
39
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 34 publications
3
39
2
Order By: Relevance
“…In the present study, the mortality rates observed following anastomotic leakage are similar to those of other recently published studies on population‐based data . The association between anastomotic leak and increased postoperative mortality is reasonable pathophysiologically, and has been shown previously for colorectal surgery .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, the mortality rates observed following anastomotic leakage are similar to those of other recently published studies on population‐based data . The association between anastomotic leak and increased postoperative mortality is reasonable pathophysiologically, and has been shown previously for colorectal surgery .…”
Section: Discussionsupporting
confidence: 91%
“…The ambiguity in the term anastomotic leakage is problematic for all research aimed at quantifying the rate of leakage. The registry used allows the surgeon to define leakage arbitrarily, thereby threatening the validity of the data on which this study was based.…”
Section: Discussionmentioning
confidence: 99%
“…Estimation of the severity of the leakage with type of intervention is well established . Our finding of re‐laparotomy (ISREC C) being a risk factor for permanent stoma, although implicating that the severity of anastomotic leakage predicts the end result of permanent stoma, has to be interpreted considering the type of intervention performed during laparotomy.…”
Section: Discussionmentioning
confidence: 92%
“…A defunctioning stoma can reduce the morbidity of anastomotic leakage and reduce the need for urgent reoperation [3,[24][25][26], although widespread implementation has been questioned given reports of unchanged leak rates despite routine use [27], longer hospital stay and stoma-related complications [28,29]. A defunctioning stoma is also reported to alleviate the symptoms of anastomotic leakage, promote anastomosis-preserving therapy and facilitate nonoperative treatment [30]. This ameliorating effect is confirmed in our study, but a defunctioning stoma from the index procedure is not related to the final outcome of permanent stoma among patients with manifest anastomotic leakage.…”
Section: Discussionmentioning
confidence: 99%
“…The ISREC classification, founded on the need for re-intervention [8], is useful for understanding reasons for different AL outcomes. AL patients with a diverting stoma have a better clinical course and less frequently need a reoperation [11,24]. In low ARs a defunctioning stoma appears to mitigate the effect of an AL [14,15].…”
Section: Discussionmentioning
confidence: 99%